Measuring quality of life in Latin America: What happiness research can (and cannot) contribute - Carol Graham (Inter-American Development Bank, Research Department, 2008)
This paper the issues involved in taking a broader, quality of life-based approach rather than an income-based approach to assessing welfare. Using tools provided by the economics of happiness and relying on both large-scale surveys and field research in Latin America, the paper shows how a quality of life approach can help to evaluate the welfare effects of factors ranging from health, education, and unemployment status to institutional arrangements such as inequality and opportunity. Nonetheless, directly inferring policy implications from the results is problematic because of factors including norms and expectations based on differences in the way individuals answer questions to surveys and lack of clarity in the definition of happiness. The latter allows for research comparisons across individuals and cultures but presents challenges as a basis for policymaking.
Keywords: 330; Lebensqualität; Sozialer Indikator; Messung; Lateinamerika